Pengaruh Zakat Terhadap Indeks Pembangunan Manusia dan Tingkat Kemiskinan Mustahik : Studi Kasus Pendayagunaan BAZNAS Kota Bogor - Rina Murniati; Irfan Syauqi Beik (AL-MUZARA'AH, 2014)
This research aims at analyzing zakat distribution program of BAZNAS of Bogor City and its impact towards mustahik life based on the income changes after zakat and the values of post-zakat Human Development Index (HDI) and poverty reduction. By utilizing t-statistics, individual HDI, and poverty indicators, this study concludes that zakat has positive impact in increasing human development of mustahik in Bogor city. T-statistics result shows that theres is significant impact of zakat on the mustahik income. HDI value indicates that there is an increase from 47 to 49 in the presence of zakat. As for poverty indicators, all indices used portray significant reduction in the poverty level of mustahik. This could be observed from the reduction in the values of headcount ratio index (H), poverty gap index (P1), income gap indeks (I), and Sen indeks of poverty (P2), respectively.